2000
DOI: 10.1002/1097-0282(200011)54:6<379::aid-bip20>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Peptides containing the sulfonamide junction. 2. Structure and conformation of Z-Tau-Pro-D-Phe-NHiPr

Abstract: The taurine (Tau) containing N‐protected pseudotripeptide isopropylamide Z–Tau–Pro–D‐Phe–NHiPr (1) has been specifically designed and synthesized as suitable model to test the ability of the sulfonamido group to participate as H‐bond acceptor to a type II β‐turn and to get information on the preferred rotameric conformation around the S—N bond and the hybridization state of the nitrogen atom. The present structural investigation reveals that, although the sulfonamide junction is invariably folded in a gauche m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…In contrast to the relatively rigid amide peptide bond, the sulfonamide bond is more freely rotatable and the cis-trans isomerism is not observed [127,130]. This greater rotational freedom allows for the sulfonamide oxygens to assume a variety of positions, where one oxygen occupies a cis or trans orientation with respect to the amide N-H, while the other oxygen is in neither a cis nor trans When compared to the amide moiety, the sulfonamide group is a stronger hydrogen bond donor [127] and the sulfonamide N-H is more acidic than the amide N-H, but a weaker hydrogen bond acceptor [127][128][129]. Furthermore, the hydrogen bond accepting character of the sulfonamide moiety is split between two accepting sites due to the two sulfonamide oxygens.…”
Section: Substitution Of Amides With Sulfonamidesmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the relatively rigid amide peptide bond, the sulfonamide bond is more freely rotatable and the cis-trans isomerism is not observed [127,130]. This greater rotational freedom allows for the sulfonamide oxygens to assume a variety of positions, where one oxygen occupies a cis or trans orientation with respect to the amide N-H, while the other oxygen is in neither a cis nor trans When compared to the amide moiety, the sulfonamide group is a stronger hydrogen bond donor [127] and the sulfonamide N-H is more acidic than the amide N-H, but a weaker hydrogen bond acceptor [127][128][129]. Furthermore, the hydrogen bond accepting character of the sulfonamide moiety is split between two accepting sites due to the two sulfonamide oxygens.…”
Section: Substitution Of Amides With Sulfonamidesmentioning
confidence: 99%
“…Consequently, peptides containing sulfonamide substitutions have been investigated as transition state isosteres for the use as protease inhibitors [126]. When compared to the amide moiety, the sulfonamide group is a stronger hydrogen bond donor [127] and the sulfonamide N-H is more acidic than the amide N-H, but a weaker hydrogen bond acceptor [127][128][129]. Furthermore, the hydrogen bond accepting character of the sulfonamide moiety is split between two accepting sites due to the two sulfonamide oxygens.…”
Section: Substitution Of Amides With Sulfonamidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigation results revealed that, although the sulfonamide junction was invariably folded in a gauche mode, the β-turn structure was not found in the crystal and the sulfonamido oxygen atoms were not involved in any intra-or intermolecular hydrogen-bond interactions. The Pro nitrogen was significantly pyramidalized and the nitrogen lone pair pointed in the opposite direction to that of the Pro Cα-H bond thus adopting R chirality, in an arrangement practically identical to that found in the previously studied homochiral analogue Z-Tau-Pro-Phe-NH i Pr (Scheme 19) 64. The sulfonamide modified RGD analogs were synthesized from Z-Tyr-OH.…”
mentioning
confidence: 64%
“…Consequently, peptides containing sulfonamide substitutions have been investigated as transition state isosteres for the use as protease inhibitors [126]. When compared to the amide moiety, the sulfonamide group is a stronger hydrogen bond donor [127] and the sulfonamide N-H is more acidic than the amide N-H, but a weaker hydrogen bond acceptor [127][128][129]. Furthermore, the hydrogen bond accepting character of the sulfonamide moiety is split between two accepting sites due to the two sulfonamide oxygens.…”
Section: Substitution Of Amides With Sulfonamidesmentioning
confidence: 99%